2012
DOI: 10.1177/0300985811429812
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Ferret Model for Pneumonia From Seasonal Human Influenza A Virus Infection

Abstract: The primary complication of seasonal influenza in humans is viral pneumonia. A conventional animal model-intranasal inoculation of ferrets with 10 6 median tissue culture infectious dose of virus-results in disease that is neither consistent nor comparable with severe viral pneumonia in humans. Therefore, the authors modified the experimental procedures by increasing the median tissue culture infectious dose to 10 9 and by inoculating via the intratracheal route, testing these procedures with H1N1 strains (A/ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Differences of this magnitude were rarely observed in the 1.0-ml inoculum group, demonstrating that the largest inoculum volume resulted in more uniform viral replication in the LRT, likely a result of a more uniform distribution of the inoculum. van den Brand et al (31) reported inconsistencies in the ability to elicit clinical signs of disease in ferrets using a seasonal human influenza virus administered intranasally at a dose of 10 6 TCID 50 . Thereafter, they modified their experimental design to intratracheal administration of 10 9 TCID 50 of virus in an inoculum volume of 3 ml.…”
Section: Discussionmentioning
confidence: 99%
“…Differences of this magnitude were rarely observed in the 1.0-ml inoculum group, demonstrating that the largest inoculum volume resulted in more uniform viral replication in the LRT, likely a result of a more uniform distribution of the inoculum. van den Brand et al (31) reported inconsistencies in the ability to elicit clinical signs of disease in ferrets using a seasonal human influenza virus administered intranasally at a dose of 10 6 TCID 50 . Thereafter, they modified their experimental design to intratracheal administration of 10 9 TCID 50 of virus in an inoculum volume of 3 ml.…”
Section: Discussionmentioning
confidence: 99%
“…Although a larger inoculum volume (1 ml) is associated with more consistent LRT replication than that with the small volume used in our study (0.5 ml), all lung lobes were collected and analyzed in our study, minimizing any sampling bias associated with dosing, as previously reported (48). Furthermore, while we cannot completely rule out that the inability to detect growth of A(H3N2) or influenza B virus in the LRT was due to intranasal inoculation, others have reported only limited replication of a 2008 A(H3N2) virus in the LRT when dosed intratracheally in a ferret model of pneumonia (49). Assessments of cytokine and chemokine profiles following infections with other seasonal influenza virus strains are also of interest.…”
Section: Discussionmentioning
confidence: 97%
“…All three influenza virus strains had been directly derived from patient isolates. For seasonal influenza, H3N2 virus (A/Netherlands/177/2008) [18], for pandemic influenza, pH1N1 influenza virus (A/Netherlands/602/2009) [44] and for highly pathogenic avian influenza virus (HPAI) the H5N1 strain (A/Indonesia/5/2005) were used [45]. Virus stocks were passaged three times in Madin-Darby Canine Kidney (MDCK) cells and titrated according to standard methods.…”
Section: Methodsmentioning
confidence: 99%
“…The laboratory ferret ( Mustela putorius furo ) is not only susceptible to human isolates of seasonal, avian and pandemic influenza viruses, but pathogenesis and severity of the respective clinical manifestations of these infections are to a large extent similar to those found in humans [18,19]. Therefore, to address the hypothesis that humans at risk for vascular disease may develop clinically overt vascular thrombosis during or shortly after influenza virus infection [20], we collected plasma samples during a time course pathogenesis experiment in which ferrets were infected with seasonal-, avian- or pandemic influenza viruses [21].…”
Section: Introductionmentioning
confidence: 99%